2014
DOI: 10.1038/ncomms6038
|View full text |Cite
|
Sign up to set email alerts
|

Gigahertz single-trap electron pumps in silicon

Abstract: Manipulation of single electrons is the key to developing ultimate electronics such as single-electron-based information processors and electrical standards in metrology. Especially, high-frequency and high-accuracy single-electron pumps are essential to realize practical current standards. While electrically defined quantum dots are widely used to build single-electron pumps, a localized state in semiconductors is also a potential candidate for accurate pumps because it can have a large activation energy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 42 publications
3
85
0
1
Order By: Relevance
“…Pumping through a single donor atom at a much higher rate of 1 GHz was demonstrated by Tettamanzi et al [73] at T = 4.2 K. Yamahata et al argue in [74] that the use of charge trap levels as the quantization-defining localized states may lead to higher operation frequencies and precision. By electrically controlling the capture and emission rates to and from a trap level the authors of [74] have demonstrated quantized pumping up to the frequency of 3.5 GHz with a transfer accuracy of about 10 −3 , limited by their measurement uncertainty. The device operated at a temperature of T = 17 K.…”
Section: Tunable-barrier Pumpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pumping through a single donor atom at a much higher rate of 1 GHz was demonstrated by Tettamanzi et al [73] at T = 4.2 K. Yamahata et al argue in [74] that the use of charge trap levels as the quantization-defining localized states may lead to higher operation frequencies and precision. By electrically controlling the capture and emission rates to and from a trap level the authors of [74] have demonstrated quantized pumping up to the frequency of 3.5 GHz with a transfer accuracy of about 10 −3 , limited by their measurement uncertainty. The device operated at a temperature of T = 17 K.…”
Section: Tunable-barrier Pumpsmentioning
confidence: 99%
“…Universal, analytic results are possible only in special limits, of which a particularly useful one is the statistics of charge capture [52,108,111,124,[145][146][147] (see also an analytic solution for time-limited emission with constant rates in [74,96,148,149]). To model charge capture in a QD by a closing tunable barrier, we follow [147] and consider a close-enough-to-equilibrium initial state of the dot at t = t 0 , when it is well connected to the source lead.…”
Section: Theory Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability to manipulate individual electrons leads to several applications. Metrologists have pursued electron-counting standards for capacitance [1,2] and current [3][4][5][6][7][8][9][10] since the realization of SEDs. Others have worked to perform logic or memory applications with SEDs because of the prospect for doing so at very low power [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Проектируются и создаются ключе-вые элементы микросхем, в которых активный элемент реализуется несколькими или даже одним атомом. Были продемонстрированы прототипы одноатомных одноэлек-тронных устройств: квантового бита [5][6][7], квантово-го логического вентиля [8], устройств для квантовой метрологии [9,10], сверхчувствительных зарядовых сен-соров для биологических применений [11]. Точность моделирования распределения внедряемой примеси по глубине будет в значительной мере определять рабочие характеристики элемента микросхемы.…”
Section: Introductionunclassified